Plant Embryogenesis - Ueda, Minako; Kurihara, Daisuke (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Despite intense investigation of plant embryogenesis, there are still various open questions in this fascinating field. For example, our knowledge is still poor in relation to the spatiotemporal dynamics and the regulatory mechanisms of various embryonic events at all levels of whole plants, organs, tissues, cells, and molecules. We also need to understand the generality and diversity of embryonic features in a diverse range of species and also the bioengineering technologies to improve reproductive traits. Therefore, in this Special Issue, we show various articles, including original research papers and reviews, to expand our knowledge on plant embryogenesis, including works spanning from the various novel protocols of model plants to the regulations of somatic embryogenesis in agricultural plants.